Dampak Implementasi Pembelajaran Berbasis Digital terhadap Motivasi Belajar Siswa - Nabila Fri Cahyani; Silvia Mahrani; Debora Matanari; Ruth Hanna Apriani Sihombing; Jamaludin Jamaludin; Sri Yunita (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2025)
Technological advancements have significantly influenced learning methods, including the implementation of digital-based learning. This study aims to analyze the impact of digital-based learning implementation on students' learning motivation. Using a descriptive qualitative approach, data were obtained through observations, interviews, and documentation with teachers as research subjects. The findings indicate that digital-based learning positively affects students' learning motivation by increasing their engagement through interactive media such as educational videos and gamification platforms. However, challenges such as infrastructure limitations and potential digital distractions were also identified. Therefore, appropriate strategies are needed to optimize the use of digital technology to enhance learning effectiveness and student motivation optimally.